The impact of mobile social network sites on social trust: evidence from the China - Jiankun Liu; Yueyun Zhang (Humanities & Social Sciences Communications)
Abstract The development of digital technology and its potential influence on social capital has become a nascent research topic, but scholars have been focusing on the role of Internet use and presented inconsistent findings. Our study improved the social capital theory and focused on online social networks based on mobile social network sites (SNS) and their shifts to offline social networks in the accumulation of social capital. Using a nationally representative Chinese sample from the Chinese General Social Survey (N = 12,010), we examined the relationship between WeChat, the most popular mobile SNS in China, and social trust and explored the mediating effect of offline social networks in the above association. The results indicated that WeChat use positively influenced individuals’ social trust, but the positive effect was not distributed among individuals, i.e., young adults, high-education adults, and urban residents gained more benefits from WeChat use. Moreover, WeChat use could promote social trust by enhancing individuals’ offline social networks. These findings helped to elucidate the linkage between mobile SNS use and social trust and uncover the formation mechanisms of social capital in the digitalized era.